Mineralogical, numerical and analytical studies of the coupled oxidation of pyrite and coal - Evans, Katy; Gandy, C.; Banwart, S. (The Mineralogical Society, 2003)
Mineralogical, bulk and field leachate compositions are used to identify important processes governing the evolution of discharges from a coal spoil heap in County Durham. These processes are incorporated into a numerical one-dimensional advective-kinetic reactive transport model which reproduces field results, including gas compositions, to within an order of magnitude. Variation of input parameters allows the effects of incorrect initial assumptions on elemental profiles and discharge chemistry to be assessed. Analytical expressions for widths and speeds of kinetic reaction fronts are developed and used to predict long-term development of mineralogical distribution within the heap. Results are consistent with observations from the field site. Pyrite oxidation is expected to dominate O2 consumption in spoilheaps on the decadal timescale, although C oxidation may stabilize contaminants in effluents on the centennial scale.